The Influence of Celebrity Endorsers and E-WOM on Purchase Decisions of Skintific with Brand Image as an Intervening Variable in Jakarta - Viniyati Maftuchach; Citra Alifia Yulianti; Lela Nurlaela Wati (Asosiasi Dosen Muda Indonesia, 2025)
A marketing tactic that can influence purchasing decisions is Celebrity Endorsement and electronic word-of-mouth. The purpose of this study is to evaluate how electronic word-of-mouth and celebrity endorsements affect consumer behavior. decisions in Jakarta that use brand image as a mediating factor. The SEM-PLS technique is used in this study's descriptive quantitative methodology. The application utilized is SmartPLS version 4.0.0, employing sample data from 140 respondents via questionnaire distribution. The findings show that celebrities who endorse products exert a positive and significant impact on purchase decisions, whereas electronic word of mouth lacks a considerable effect on synthetic purchasing decisions. Moreover, Brand Image can serve as a mediator in the impact of celebrity endorsers. Electronic word-of-mouth influences purchasing decisions for skincare product in Jakarta. This research is limited to Skintific users in DKI Jakarta so the results may not be generalizable to a wider population. Apart from that, this research only considers the variables of celebrity endorser, E-WOM, and brand image, without examining other factors that might influence purchasing decisions. This research provides new insight into how celebrity endorsers and electronic word of mouth can be used in marketing strategies for skincare products. Apart from that, this research can also be a reference for companies that are formulating more effective marketing and branding strategies.